Articulações entre os interesses dos alunos e livros didáticos: a voz do estudante na construção curricular de ciências - Amestoy, Micheli Bordoli (2015)
The aim of this dissertation was to identify how the 'Student Voice' makes part of the construction of the science curriculum, the development of Reference Matrix ENEM and of the preparation of textbooks in the high school biology. This work is organized in 3 chapters in article format, in order to address in more detail the issues that make up this research. The first article investigated the jobs that have been made in recent years about textbook and School Curriculum and mapped the contributions of the views of students in the construction of the Science Curriculum. The second article sought relations between the interests of high school students resulting from the application - in nationwide, an instrument entitled The Relevance of Science Education (ROSE) and the skills assessed in ENEM, analyzed from its Reference Matrix. The third and final article aims to investigate how often the topics of greatest interest to high school students appear in Biology textbook. From this, the need arises to study whether there is relationship between the triad: Interests of students, Textbook and Curriculum. This is because we believe that there should be a balance in the process of (re) construction curriculum in which students leave the facilitating role to become active participants in this process. Listen students provides a major change in decision-making and educational activities geared for whom education is designed. The set of three articles showed us that researches on 'Student Voice' are very important for the development of new curricular and pedagogical strategies. However, there are a greater number of researchers engaged on the subject abroad than in Brazil. We showed the almost null student participation in decisions, discussions or even meetings on changes, menus and curricular reforms. In conclusion, it is necessary to increase the number of jobs and new research about the 'Student Voice', in order to valorize the information given by young people. It is noticed that some of the interests of young people, analyzed, appear very superficially in some of the selected collections. With the present results, we can suggest the need of new researches about the quality of textbook. These can not only identify possible deficiencies and refine future training structures of textbooks, but can also become important tools to arise books with a new look for Science Education.